Jane Tolmach for Assembly Press Release (1976)
This February 17, 1976 press release announces that Oxnard City Councilwoman and former mayor Jane Tolmach filed to run for the 36th Assembly District seat being vacated by Ken MacDonald. She emphasizes effective representation in Sacramento, pledging to secure Ventura County's fair share of state revenues for transportation, mental health, and education. Tolmach identifies the establishment of a four-year college in Ventura County as a key priority and commits to working with Senator Omer Rains to achieve it. She also highlights her independence from outside business interests and states that tax reform—particularly preventing a shift back to regressive local property taxes—is the most urgent issue facing California.